2021
DOI: 10.3390/mi12050524
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of a Microscale Piezoelectric Vibrator Based on Electrohydrodynamic Jet Printed PZT Thick Film

Abstract: This paper proposes a novel way of preparing a PZT thick film micro vibrator using the electrohydrodynamic jet (E-Jet) printing technique. Initially, a micro piezoelectric vibrator was simulated and designed for obtaining optimized structure, which has a total thickness of less than 600 µm. Subsequently, the PZT thick film element was directly printed on the elastic body using the E-Jet printing. This method avoids the glue fabrication process involved in the bulk piezoelectric fabrication, thus avoiding the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…[156][157][158] Printed structure changes their shape when they absorb water and recover their original shape after drying. [159][160][161] Furthermore, this shape change behavior also stimulates the low Tg, and consequently, the shape recovery process takes place. In the same context, Ren et al [162] proposed a 4DP technique under both water and temperature stimuli-responsive shape-shifting behavior of PUbased elastomer material.…”
Section: Moisture-based Stimulusmentioning
confidence: 98%
See 1 more Smart Citation
“…[156][157][158] Printed structure changes their shape when they absorb water and recover their original shape after drying. [159][160][161] Furthermore, this shape change behavior also stimulates the low Tg, and consequently, the shape recovery process takes place. In the same context, Ren et al [162] proposed a 4DP technique under both water and temperature stimuli-responsive shape-shifting behavior of PUbased elastomer material.…”
Section: Moisture-based Stimulusmentioning
confidence: 98%
“…[ 156–158 ] Printed structure changes their shape when they absorb water and recover their original shape after drying. [ 159–161 ] Furthermore, this shape change behavior also stimulates the low Tg, and consequently, the shape recovery process takes place. In the same context, Ren et al.…”
Section: Stimuli Responses In 4d Printingmentioning
confidence: 99%
“…Each of the motors, placed on the forearm, was intended to represent pressure on a specific fingertip. Pressure can also be generated through piezoelectric thick-film vibrators [13], where a change in length is induced perpendicular to the skin. These actuators are based on the inverse piezoelectric effect, in which a change in the length of the piezoelectric crystal can be induced by applying voltage [13].…”
Section: Related Workmentioning
confidence: 99%
“…The research findings reported in the 3D-Printed Actuators Special Issue show promising approaches for engineering biology-like actuation. These findings have led to the following: the creation of an anatomically correct robotic hand with human-like grasping capabilities [ 1 ]; emulation of an antagonistic variable stiffness actuation observed in the musculoskeletal system of snakes [ 2 ]; reducing friction in rotating parts and joints by combining 3D printing and radiation pressure [ 3 ]; fabrication of flexible piezoelectric composite actuators without application of any adhesives [ 4 ]; extension of the service life of actuators through geometric and material optimization [ 5 ]; and acceleration of print inspection through an open-source low-power computer-vision hardware [ 6 ].…”
mentioning
confidence: 99%
“…The typical fabrication involves complex manufacturing processes such as photolithography, etching, sol-gel, and sputtering. Using a cost-effective electrohydrodynamic (E-Jet) printing, Wang et al applied PZT film directly to elastic structures, followed by co-firing sintering to form PZT actuators [ 4 ]. Their method eliminated the use of adhesives—thus overcoming the limits of voltage drops, and absorbing amplitude in current PZT actuators.…”
mentioning
confidence: 99%